Plan de negocio para la producción y exportación de snacks nutricionales a base de cereales acompañados de uvilla y maracuyá hacia California, Estados Unidos - Vergara Arias, Ana Valeria (2018)
The purpose of this business plan is determine the viability of create an Ecuadorian company that produces, sells and exports healthy bars called "nutritional snacks" made with cereals, passion fruit and golden berry. For implement the proposed project, important factors were considered that determined the feasibility and acceptance of this product. Important variables of the external environment were analyzed like political, economic, social and technological that reflected important data such as trade relations between the United States and Ecuador, finding the Tariff Preference System which applicate frees tariffs on more than two thousand products to enter into the American market, which is currently part of the population with new consumption habits, causing that 3% stop consuming cereals because of the high amount of sugar and they are looking for new low-calories products such as nutritious bars or snacks that have exotic fruits. The manufacturing or production sector represents 69.2% of the Ecuadorian GDP, which is the most important for the country. In the US industry, strong competitors were identified such as General Mills, which had a 9% growth in sales of its "Nature Valley" cereal bars, and other cereal bars such as "Kellog s special" and "Tosh" experienced 1%. On the other hand, the Ecuadorian industry identified excellent suppliers such as Moderna S.A, Cereales Andino and Expofrut who offer quality in their products since they have great experience in the market. When analyzing the factors that intervene in the execution of the business plan, "Passion Go Fit" is created, which when focusing on a market like the United States, finds a stable environment for its commercialization, and identifies a niche that seeks healthy and sustainable food for their consumption called "LOHAS". The organizational structure allowed to determine the necessary machinery for the production of nutritional snacks, in the same way the necessary human capital was identified giving a highlight of 7 expert people in different areas. In the production process, a time of 1.20 minutes was estimated for the elaboration of 50 cereal bars. With respect to the financial plan, an initial investment of around $ 76,047.00 was obtained. On the other hand, the statement of results, statement of financial position, cash flow statement, cash flow projected cash flow of the investor, which allowed to obtain the NPV, IRR, IR.